Study on the Stability of Salicin in the Dissolution Process - Suo, J.L. (Asian Journal of Chemistry, 2011)
Salicin's dissolution behaviour in saline solution were studied by a micro-calorimetric method. The measured integral and differential heat of solution (DsolHm and DdifHm) were used to build equations of the solute and the heat, so that dissolution thermodynamic equations DsolHm, DsolGm and DsolSm were achieved. The current study provides theoretical bases for clinical applications of salicin.